2006
DOI: 10.1111/j.1741-6612.2006.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional interdependence

Abstract: Objective:  The interrelationship between functional capacity, informal networks and the physical environment of the residence and residential location is used to describe age‐care service utilisation and non‐utilisation. Methods:  Fifty‐two applicants for home‐care services were matched with 52 non‐applicants, and 40 applicants for day‐care services were matched with 40 non‐applicants according to age, gender, mental status, and physical functioning. Results:  Discriminant Function Analyses indicated home‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Varying levels of social support outside day centres were reported in five studies (Del Aguila, Cox and Lee 2006, Fulbright 2010, Iecovich and Carmel 2011, Chaichanawirote and Higgins 2013, Wittich, Murphy and Mulrooney 2014). Having an inadequate informal network was one of two factors found to contribute to the decision to apply for a day centre place (Del Aguila, Cox and Lee 2006). Caiels, Forder and Malley’s (2010) English study reported some volunteering activity (with no details) and only one attender in a Norwegian study also attended a course (unspecified) elsewhere (Lund and Engelsrud 2008).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Varying levels of social support outside day centres were reported in five studies (Del Aguila, Cox and Lee 2006, Fulbright 2010, Iecovich and Carmel 2011, Chaichanawirote and Higgins 2013, Wittich, Murphy and Mulrooney 2014). Having an inadequate informal network was one of two factors found to contribute to the decision to apply for a day centre place (Del Aguila, Cox and Lee 2006). Caiels, Forder and Malley’s (2010) English study reported some volunteering activity (with no details) and only one attender in a Norwegian study also attended a course (unspecified) elsewhere (Lund and Engelsrud 2008).…”
Section: Resultsmentioning
confidence: 98%
“…They maintained or improved physical function and quality of life, impacting on their attenders’ potential ability to remain independent (Henwood, Wooding and de Souza 2013, Battaglia et al 2014, Ota et al 2014, Yamada and Demura 2014). These findings are particularly pertinent since people may initially access day centres when their functional capacity and support network have reduced (Del Aguila, Cox and Lee 2006). Thus, day centres may replace rather than supplement informal support.…”
Section: Resultsmentioning
confidence: 99%
“…As stated by Del Aguila et al (2006), the life context plays an important role because ''performance limitations requiring assistance arise from the interrelationship between impaired (cognitive and physical) functional capacity and challenges presented by the immediate physical context of the residence and the extended physical environment of the residential location' ' (p. 134). Given that many older people spend most of their time in the residential environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid aging of the global population, represented by the number of about 901 million over-60 year olds worldwide (Global AgeWatch Index, 2015), has dramatically increased the risk of health problems in older adults (World Health Organization, 2013), thus enhancing the need for long-term care in this population (Cavrini et al, 2010). Current European policies on housing for the elderly focus mostly on remaining at home for as long as possible, even though both the decline in health and the lack of an informal network of assistance might transform one's home into a confined and unsuitable place (Del Aguila, Cox, & Lee, 2006;Rubinstein & De Medeiros, 2004). Thus, alternative solutions, such as relocation to a long-term facility, need to be considered.…”
mentioning
confidence: 99%